Hallen og havet som eskatologiske modsætninger - i den angelsaksiske poesi og hos Grundtvig - Bøye, Merete (Grundtvig-studier, 1998)
The Sea and the Hall as Eschatological Opposites By Merete Bøye Grundtvig frequently uses the Anglo-Saxon (AS) hall (heall) as a symbol of Paradise or of the Church. The hall is described by Beowulf-expert Andreas Haarder as a life-centre, where the AS king and his men gather around the feast, the giving of gifts, and the song of the scald. The opposite of the hall is the un-settling surrounding ’outside’, which is nature. The hall exists wherever and whenever men gather together in fellowship, and is as such potentially eternal. But it is always exposed to outer threat. The force of nature which awed the Anglo-Saxons most of all was the sea, which - being a seafaring nation - they had learned to fear and respect. To the Anglo-Saxons, the sea was a hostile and almost invincible evil power that only a true hero - such as Beowulf - could hope to conquer. The sea was the force which separated us from Paradise, but also the force which you had to defy in order to reach Paradise.Henning Høirup has observed a similar relation between fellowship and outer threat in Grundtvig’s writings. In Fra døden til livet (From Death to Life), Høirup writes that life - to Grundtvig - is to fill your place in the fellowship for which God has created us. Death will try to force itself onto the fellowship and dissolve it. Høirup’s concepts of life and death correspond with the AS concepts of the hall and the sea.In the works of Grundtvig, AS sea-imagery often occurs, e.g. in De Levendes Land (The Land of the Living), where Paradise is described as » Landet bag Hav« (the land behind the sea), and in Grundtvig’s sermons based on Matthew 8, 23-27, where he likens the church to a ship carrying its passengers to Paradise. The helmsman of the ship is Christ or the Holy Ghost.In the article The First New European Literature (1993), S.A.J. Bradley also points to AS influence on Grundtvig’s last poem Gammel nok er jeg nu blevet (Old Enough I Now Have Grown), which holds the same kind of sea-imagery as Grundtvig used in the sermons mentioned. Especially the AS poem The Seafarer« is very similar to Gammel nok... Both The Seafarer and Gammel nok... tell of an old man, who is crossing a vast, hostile ocean on a ship. The destination is Paradise. At the end of both poems there is a passage of praise to the Lord. This article concludes that Gammel nok... may be inspired by the AS seafaring poems.